Superabsorbent Polymers: High Capacity Functionalized Protein Superabsorbents from an Agricultural Co‐Product: A Cradle‐to‐Cradle Approach (Adv. Sustainable Syst. 9/2020). (10th September 2020) - Capezza, Antonio Jose; Cui, Yuxiao; Numata, Keiji; Lundman, Malin; Newson, William Roy; Olsson, Richard Tobias; Johansson, Eva; Hedenqvist, Mikael Stefan
Abstract : The development of environmentally‐friendly materials for the growing superabsorbent polymer industry is essential. In article number 2000110, Antonio Jose Capezza, Mikael Stefan Hedenqvist, and co‐workers use a readily available protein co‐stream functionalized with green and harmless reagents as a sustainable alternative for the fabrication of liquid‐absorbent materials. The potential applications are many, and include single‐use disposable products such as diapers.